Optimization of Patrol Samapta Turjawali Unit to Prevent the Crime of Motor Vehicle Theft in the Jurisdiction of Klaten Police - Kriesna, Dhimas (Advances in Police Science Research Journal, 2024)
The author raises the final assignment with the problem of “Optimization of Patrol Samapta Unit Turjawali to Prevent the Crime of Motor Cycle Theft in the Jurisdiction of Klaten Police”. The writing of this final project aims to identify a series of patrol activities of the Turjawali Unit of the Klaten Police Samapta Unit. This writing uses a qualitative approach with a descriptive type of research by conducting informant interviews, observation, and document studies. In addition, the data used is also obtained from various references such as articles, journal books and online media news that are relevant to the problem variables discussed. The writing uses management theory and SWOT analysis theory as well as several concepts relevant to the problem, namely the concepts of patrols based on Perkabaharkam Number 1 of 2017 concerning Patrols. The Klaten Police Samapta Unit is the backbone of preventive police action in preventing criminal acts in the jurisdiction of the Klaten Police, especially the motor vehicle theft. In patrol activities by the Turjawali Unit of the Klaten Police Samapta Unit, there are still some shortcomings in terms of planning, organizing, actuating, and controlling which are not in accordance with the Patrol SOP which has been regulated in Perkabaharkam Number 1 of 2017 concerning patrols. In addition, there are factors that influence both internally and externally so that the patrol activities of the Turjawali Unit of the Samapta Unit cannot be carried out optimally. From the conclusions drawn, the management stages and resources owned by the Turjawali Unit of the Samapta are still not optimal because there are several stages that are not in accordance with the rules of Perkabaharkam Number 1 of 2017. Therefore, to improve the implementation of patrol activities, creative breakthrough innovations are needed in an effort to improve the implementation of patrols.